The efficacy of audiovisual distraction as an anxiety-minimizing technique during echocardiography in preschool children - Yantie, Ni Putu Veny Kartika; Gunawijaya, Eka; Windiani, I Gusti Ayu Trisna; Maharini, Kadek (Paediatrica Indonesiana, 2023)
Background Echocardiography procedures can cause fear and anxiety in children, especially at preschool age. Audiovisual distraction is a simple, harmless, and low-cost technique that does not interfere with the procedure. Objective To assess the effect of audiovisual distraction on the anxiety levels of children aged 2-5 years during echocardiography. Methods This quasi-experimental study included children aged 2-5 years who were admitted for echocardiography. Patients with hearing or visual impairment, Down syndrome, autism, or attention-deficit/hyperactivity disorder were excluded. We administered anxiety-reducing intervention in the form of cartoon audiovisual media shown on a ceiling-mounted television during the echocardiography procedure. Anxiety levels were assessed using the Visual Analogue Scale - Anxiety (VAS-A) before and after the intervention was given. We compared the subjects’ pre- and post-procedure VAS-A scores and heart rates. Results Of the 43 subjects who underwent echocardiography during the study period, the mean age was 3.2 (SD 0.9) years, with an equal sex distribution. Most subjects had a history of repeated echocardiography procedures and hospitalizations. Thirty-nine (90.6%) of subjects demonstrated anxiety during the echocardiography procedure. There was a significant mean difference of 11.9 (SD 13.2) bpm (95%CI 7.8 to 15.9 bpm, p<0.001) in heart rate pre- vs. post-intervention. Median pre- and post-intervention VAS-A scores were 5 (range 0-10) and 1 (range 0-4), respectively (P=0.001). Post-intervention, almost all (97.7%) subjects had no or mild anxiety. Conclusion Audiovisual content presented on television serves as an effective distraction method to reduce children's anxiety during echocardiography.